Prospective evaluation of lipid management following acute coronary syndrome in non-Western countries (2021)
Background: Half the global burden of cardiovascular disease (CVD) is concentrated in the Asia-Pacific (APAC) region. Hypothesis: Suboptimal control of low-density lipoprotein cholesterol (LDL-C) may play a large role in the burden of CVD in APAC and non-Western countries. Methods: The Acute Coronary Syndrome Management (ACOSYM) registry is a multinational, multicenter, prospective observational registry designed to evaluate LDL-C control in patients within 6 months after hospitalization following an acute coronary syndrome (ACS) event across nine countries. Results: Overall, 1581 patients were enrolled, of whom 1567 patients met the eligibility criteria; 80.3% of the eligible patients were men, 46.1% had ST-elevation myocardial infarction, and 39.5% had non-ST-elevation myocardial infarction. Most (1245; 79.5%) patients were discharged on a high-intensity statin. During the followup, only 992 (63.3%) patients had at least one LDL-C measurement; of these, 52.9% had persistently elevated LDL-C (>70 mg/dl). The patients not discharged on a highdose statin were more likely (OR 3.2; 95% CI 2.1–4.8) to have an LDL-C above the 70 mg/dl LDL-C target compared with those who were discharged on a high-dose statin. Conclusion: Our real-world registry found that a third or more of post-ACS patients did not have a repeat LDL-C follow-up measurement. In those with an LDL-C followup measurement, more than half (52.9%) were not achieving a <70 mg/dl LDL-C goal, despite a greater uptake of high-intensity statin therapy than has been observed in recent evidence. This demonstrates the opportunity to improve post-ACS lipid management in global community practice.